2017
DOI: 10.1038/s41467-017-00395-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of quenchable amorphous diamond

Abstract: Diamond owes its unique mechanical, thermal, optical, electrical, chemical, and biocompatible materials properties to its complete sp 3-carbon network bonding. Crystallinity is another major controlling factor for materials properties. Although other Group-14 elements silicon and germanium have complementary crystalline and amorphous forms consisting of purely sp 3 bonds, purely sp 3-bonded tetrahedral amorphous carbon has not yet been obtained. In this letter, we combine high pressure and in situ laser heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 44 publications
9
90
1
Order By: Relevance
“…The reaction sequence previously described by Narygina et al () (Fe + C n H 2n+2 → 2Fe 3 C + 3H 2 → 6FeH + 2C) was not consistently observed, as no attempt was made to evaluate this transformation with low temperature (<1,500 K) diffraction. Additionally, the obtained phase assemblage (supporting information Table S1) did not consistently indicate the presence of diamond, likely due to diamond's poor diffraction properties, particularly when synthesized at low temperatures (Zeng et al, ). Though the formation of fcc FeH X could be confirmed using at minimum the (111) and (200) peaks, the presence of iron carbide was not detected via XRD.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction sequence previously described by Narygina et al () (Fe + C n H 2n+2 → 2Fe 3 C + 3H 2 → 6FeH + 2C) was not consistently observed, as no attempt was made to evaluate this transformation with low temperature (<1,500 K) diffraction. Additionally, the obtained phase assemblage (supporting information Table S1) did not consistently indicate the presence of diamond, likely due to diamond's poor diffraction properties, particularly when synthesized at low temperatures (Zeng et al, ). Though the formation of fcc FeH X could be confirmed using at minimum the (111) and (200) peaks, the presence of iron carbide was not detected via XRD.…”
Section: Methodsmentioning
confidence: 99%
“…We speculate that the crystal-to-crystal transitions may be hindered by a large energy barrier in this system, therefore, we also performed in situ laser heating XRD measurements at highpressure (more experimental details can be found in ref. 46 ) on the (Ce,La,Pr,Sm,Y)O HEO ( Supplementary Fig. 4).…”
Section: Resultsmentioning
confidence: 93%
“…The elemental carbon-based materials adopt many forms, such as amorphous, graphite, [128] diamond, [129] etc. Carbon-based materials show a number of excellent physical and chemical properties, such as good electronic optical and mechanical properties.…”
Section: Mxene-carbon Compositesmentioning
confidence: 99%